ANALISIS PENGARUH KUALITAS LAYANAN DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Pada Pelanggan Jasa Ekspedisi JNE Express di Kota Semarang) - Sri Wahyuni; Idris Idris (Faculty of Economics and Business Diponegoro University, 2022)
The rapid development of technology in the current era, and the phenomenon of the need for goods delivery services for the community in general, including for online business people in expediting their business in sending goods within near and far reach. The increasing number of shipping services that offer the same services can encourage consumers to be able to switch to using other expedition services. So that the steps that can be taken to be able to retain customers are by improving the quality of service and brand image so that customers remain loyal to the services they use The purpose of this study was to analyze the effect of service quality and brand image on customer loyalty with customer satisfaction as an intervening variable on customers of JNE Express expedition services in Semarang City. This research uses a quantitative method with 120 respondents with a sampling method, namely non probability sampling and purposive sampling. The data collection method used in this study used a questionnaire. Data analysis using AMOS 23 tool. This study concludes that the better the service quality, the higher customer satisfaction with JNE Express. The better the brand image of service, the more customer satisfaction from JNE Express will increase. The better the quality of service provided to customers, the more loyal JNE Express customers will be. The better the brand image, the more loyal JNE Express customers will be. High customer satisfaction will be able to increase customer loyalty to JNE Express expedition services.